Auxinic herbicides induce oxidative stress on Cnesterodon decemmaculatus (Pisces: Poeciliidae) - Ruiz de Arcaute, Celeste (2019)
Pesticides might increase the production of reactive oxygen species (ROS). Dicamba (DIC) and 2,4-dichlorophenoxyacetic acid (2,4-D) are auxinic herbicides commonly applied in agroecosystems to control unwanted weeds. We analysed the oxidative damage exerted on the fish Cnesterodon decemmaculatus by an acute exposure to DIC- and 2,4-D-based herbicides formulations Banvel® and DMA®, respectively. The Endo III- and Fpg-modified alkaline comet assay was employed for detecting DNA damage caused by oxidative stress, whereas enzymatic and non-enzymatic biomarkers such as the activities of catalase (CAT), glutathione-S-transferase (GST), acetylcholinesterase (AChE), and glutathione content (GSH) were used to assess antioxidant response to these two herbicides. At the DNA level, results demonstrate that both auxinic herbicides induce oxidative damage at purines level. An increase on CAT and GST activities were detected in 48 h- and 96 h-treated specimens with both auxinics. GSH content decreased in fish exposed to DIC during 48 h and to 2,4-D after 96 h of exposure. Additionally, a diminished AChE activity in specimens treated with DIC and 2,4-D was observed only after 96 h. Total protein content decreased in fish exposed to both auxinics during 96 h. These results represent the first evaluation of oxidative damage related to DIC and 2,4-D exposure on a fish species as the Neotropical freshwater teleost C. decemmaculatus.